ANALISIS PENGENDALIAN KUALITAS MENGGUNAKAN METODE STATISTICAL QUALITY CONTROL (SQC) DALAM RANGKA MENINGKATKAN PRODUK MUTU DI PT A - Fajriah, Maulidia; Sukanta, Sukanta (Metode : Jurnal Teknik Industri, 2024)
PT. A is one of the companies engaged in assembly production, where the parts received from supplier are small component parts from subassemblt that will be sent to lines 1 and 2 tobe assembled into four-wheeled vehicle cabin chassis products in the production department. The biggest challenge at PT. A high level of product defect from production results in each department, especially in the Production Department (Trimming Assembly Line 2) for type X. This is of course will have an impact on the company, as additional time is needed to repair damage that occurs in the assembly line process and affects the non-achievement of production targets until the late release of production units. PT. A requires improvement efforts by finding the cause of defects in the product and reduce variations in the cause. Based on the result of the SQC method analysis, there are two potential causes that fall into the category of 80% of the cumulative percentage, which is the components with a percentage of 57% and loose components (loose) amounting to 24% of the total production. The problem aspects that have been analyzed focus on several areas including methods, materials, machines, and manpower